PENGARUH BRAND IDENTIFICATION, SELF-IMAGE EXPRESSION, SENSE OF NATURAL ENVIRONMENT, LAYOUT, DAN BRAND PASSION TERHADAP BRAND LOYALTY - Venesia Venesia; Margaretha Pink Berlianto (Faculty of Economics and Business Universitas Pelita Harapan, 2022)
This study aims to find a positive relationship between brand identification with brand passion, self-image expression with brand passion, sense of natural environment with brand passion, layout with brand passion, and brand passion with brand loyalty. This research is motivated by the widespread development of the retail industry throughout the world, especially in Indonesia, one of which is dominated by the H&M brand. The approach used by the researcher is a quantitative approach, obtained through the method of collecting data obtained by distributing electronic questionnaires in the form of Google Forms to 40 people in the pilot test and 272 people in the actual test. which will then be analyzed using SmartPLS 3.3.7. This research study was conducted in Indonesia, the respondents who answered the questionnaire were those who had visited the outlet at least three times and had purchased H&M product.BAHASA INDONESIA ABSTRACTPenelitian ini bertujuan untuk menemukan hubungan positif yang terjadi antara brand identification dengan brand passion, self-image expression dengan brand passion, sense of natural environment dengan brand passion, layout dengan brand passion, serta brand passion dengan brand loyalty. Penelitian ini dilatar belakangi oleh maraknya perkembangan industri retail di seluruh dunia, khususnya di Indonesia yang salah satunya didominasi oleh merek H&M. Pendekatan yang digunakan adalah pendekatan kuantitatif, diperoleh melalui metode mengumpulkan data yang didapat dengan cara menyebarkan kuesioner elektronik berupa GoogleForms. Studi penelitian ini dilaksanakan di Indonesia, responden yang menjawab kuesioner adalah mereka yang pernah mengunjungi outlet minimal tiga kali dan pernah membeli produk H&M terhadap 40 orang pada pilot tes dan 272 orang pada tes aktual. yang kemudian akan dianalisis menggunakan SmartPLS 3.3.7.